2022
DOI: 10.1111/ijn.13053
|View full text |Cite
|
Sign up to set email alerts
|

The effect of COVID‐19 pandemic on lifestyle‐related behaviours in Turkey: A web‐based cross‐sectional study

Abstract: Background The COVID‐19 pandemic and restrictions imposed to eradicate it have affected healthy lifestyle‐related behaviours. Aim The aim of this study was to determine the effect of COVID‐19 on lifestyle‐related behaviours. Methods This cross‐sectional web‐based survey research was performed with a convenience sample of 1020 adults residing in Turkey. Data were collected with self‐report data collection tools on 8–28 April 2021: a sociodemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In a study conducted with nine hundred ninety-five participants in India, it was found that the COVID-19 pandemic led to improved eating patterns, healthier foods were consumed, but physical activity decreased significantly and one-third of the participants gained weight due to an increase in screen time and sitting (Chopra et al, 2020). A study conducted in Turkey found that eating patterns, physical activity, and sleep habits were negatively affected during the COVID-19 pandemic, stress levels and cigarette consumption increased, and more than half of the participants gained weight (Korkmaz Aslan et al, 2022). In a study that examined lifestyle changes during the first wave of the COVID-19 epidemic, it was reported that 19.3% of participants shifted to a healthier lifestyle and 12.3% shifted to an unhealthy lifestyle (Werf et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a study conducted with nine hundred ninety-five participants in India, it was found that the COVID-19 pandemic led to improved eating patterns, healthier foods were consumed, but physical activity decreased significantly and one-third of the participants gained weight due to an increase in screen time and sitting (Chopra et al, 2020). A study conducted in Turkey found that eating patterns, physical activity, and sleep habits were negatively affected during the COVID-19 pandemic, stress levels and cigarette consumption increased, and more than half of the participants gained weight (Korkmaz Aslan et al, 2022). In a study that examined lifestyle changes during the first wave of the COVID-19 epidemic, it was reported that 19.3% of participants shifted to a healthier lifestyle and 12.3% shifted to an unhealthy lifestyle (Werf et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Japan, the initial case was diagnosed in January 2020, prompting the Prime Minister to declare the first state of emergency in April [2]. Subsequently, significant shifts in the behavior of people emerged as they refrained from seeking medical examinations, resulting in a profound impact on public health [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the study found that the COVID-19 epidemic negatively impacted the psychological well-being of undergraduate medical students, with increased incidence as well as levels of anxiety and stress (32)(33)(34)(35). Fourth, in terms of methods of stress relief during COVID-19, scholars have explored ways to relieve stress, such as improving lifestyle and adopting positive health behaviors (36)(37)(38)(39)(40). Mattioli et al demonstrated that isolation is associated with stress and depression, and that global action must be engendered to support healthy diet and physical activity, thereby promoting good lifestyles (41).…”
Section: Introductionmentioning
confidence: 99%